2000
DOI: 10.1530/eje.0.1420486
|View full text |Cite
|
Sign up to set email alerts
|

Resting metabolic rate, body composition, and serum leptin concentrations in a free-living elderly population

Abstract: Objective: The present study investigated the relationship between serum leptin concentrations and resting metabolic rate (RMR) in a large study group of elderly individuals with special consideration of body composition and body fat distribution as possible confounders. Design and methods: The subjects were 122 women (age: 69 Ϯ 6 years, body mass index (BMI): 26.3 Ϯ 3.6 kg/m 2 ) and 82 men (age: 69 Ϯ 5 years, BMI: 26.0 Ϯ 2.6 kg/m 2 ). RMR was measured by indirect calorimetry and body composition by the bioele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
9
12
0
Order By: Relevance
“…REEs divided by FFM (see Table 1) of this study were near by those (unit is kcal/24 h/kg, men: 28.4, women: 31.2-33.5, obese men: 29.2, obese women: 30.7) in previous studies [Tataranni et al, 1994;Weststrate et al, 1990]. Table 3 shows that REE is strongly associated with body composition (FM and FFM) and age except for in the elderly women, which supports the findings of the previous studies [Armellini et al, 2000;Karhunen et al, 1997;Luhrmann et al, 2001;Neuhauser-Berthold et al, 2000]. Thus, the REE adjusted for FFM, FM and age was used in this study.…”
Section: Discussionsupporting
confidence: 88%
“…REEs divided by FFM (see Table 1) of this study were near by those (unit is kcal/24 h/kg, men: 28.4, women: 31.2-33.5, obese men: 29.2, obese women: 30.7) in previous studies [Tataranni et al, 1994;Weststrate et al, 1990]. Table 3 shows that REE is strongly associated with body composition (FM and FFM) and age except for in the elderly women, which supports the findings of the previous studies [Armellini et al, 2000;Karhunen et al, 1997;Luhrmann et al, 2001;Neuhauser-Berthold et al, 2000]. Thus, the REE adjusted for FFM, FM and age was used in this study.…”
Section: Discussionsupporting
confidence: 88%
“…As has been shown previously, we observed a strong positive relationship between serum leptin concentrations and FM at any measured time point. [52][53][54][55] After 1 y WM, unsuccessful subjects showed an increase in their leptin concentrations compared to after weight loss, as a consequence of their regain in FM. Successful subjects did not regain FM and thus kept their leptin concentrations reduced.…”
Section: Discussionmentioning
confidence: 98%
“…The effect was such that the metabolic rates of the oldest dogs were on average only half those of dogs that were 1-2 years old. An age-related decline in resting metabolism has been reported many times for humans (Poehlman, 1993;Poehlman et al, 1993a,b;Van Pelt et al, 1997, 2001Hughes et al, 1998;Neuhauser-Berthold et al, 2000), although such declines are not universally observed (e.g. Promislow & Haselkorn, 2002;Sukhotin et al, 2002).…”
Section: Resting Metabolic Ratementioning
confidence: 97%